Mapping the Quality Excellence Position of Competitiveness of the Teacher Professional Education Program (PPG) in Five Universities in the Soloraya Region - Tukiyo Tukiyo; Purwo Haryono; Tasari Tasari; Abdul Haris; Hersulastuti Hersulastuti; Agung Nugroho Jati; Arif Julianto Sri Nugroho (Cita Konsultindo Research Center, 2024)
This study aims to determine the position of excellence of each teacher professional education program in the Soloraya region so that it can determine the right marketing strategy to satisfy and increase public interest in trusting the quality of PPG education services presented by several public and private universities that organize PPG programs. This research was conducted with a quantitative approach through multivariate multidimensional scaling statistical tests. The novelty of this research combines the concept of competitive advantage of the quality performance of PPG education service institutions in the Soloraya region through position mapping using multidimensional scalling. The population in the study were all people who had understood the quality of PPG program services in five universities. Sampling respondents using purposive sampling technique as many as 115 adult respondents. The attributes in the questionnaire were adapted from Hasanah et al including the dimensions of the quality of service of educational institutions tangibles, reliabilities responsiveness assurance and empathy. The final stage of the research has formed a map of the position of each PPG program in five universities. This activity is the beginning of efforts to create the competitiveness of each PPG program in the Soloraya region to welcome the era of achieving SDGS' goals. All of which leads to the achievement of optimal economic growth of teacher human resources in 2045.